Using complementary slackness property to solve linear programming with fuzzy parameters - Ebrahimnejad, A.; Nasseri, S. H. (Fuzzy information and engineering, 2009)
The most popular approach to handle the challenge of solving fuzzy linear programming problems is to convert the fuzzy linear programming into the corresponding deterministic linear programming. Mahdavi-Amiri and Nasseri [15,16] developed the fuzzy dual simplex algorithm to fuzzy linear programming with fuzzy parameters. In this paper, we use the complementary slackness to solve it without the need of a simplex tableau.